Developments in calcium/chemical looping and metal oxide redox cycles for high-temperature thermochemical energy storage: A review - Yan, Yongliang; Wang, Ke; Clough, Peter T.; Anthony, Edward J. (Elsevier, 2019)
Energy storage is one of the most critical factors for maximising the availability of renewable energy systems while delivering firm capacity on an as- and when-required basis, thus improving the balance of grid energy. Chemical and calcium looping are two technologies, which are promising from both the point of view of minimising greenhouse gas emissions and because of their suitability for integrating with energy storage. A particularly promising route is to combine these technologies with solar heating, thus minimising the use of fossil fuels during the materials regeneration steps. For chemical looping, the development of mixed oxide carrier systems remains the highest impact research and development goal, and for calcium looping, minimising the decay in CO2 carrying capacity with natural sorbents appears to be the most economical option. In particular, sorbent stabilisers such as those based on Mg are particularly promising. In both cases, energy can be stored thermally as hot solids or chemically as unreacted materials, but there is a need to build suitable pilot plant demonstration units if the technology is to advance.
Keywords: Calcium looping; Chemical looping; Metal oxide; Thermochemical energy storage; Carbon capture and storage